Development of Problem-Based Learning-Based Digital Teaching Materials on Biodiversity - Adzkia Maulida; Aldina Eka Andriani (JURNAL PENDIDIKAN MIPA, 2026)
This study was motivated by the fact that teachers have not been fully effective in developing technology-based teaching materials and have not incorporated audiovisual aids into their biodiversity lessons, resulting in low learning outcomes. This study aims to describe the development design and test the feasibility and effectiveness of PBL-based e-learning materials to improve learning outcomes in flora and fauna biodiversity among fifth-grade students at SDN Ngaliyan 05. This study employs an R&D approach using the ADDIE model (Analysis, Design, Development, Implementation, & Evaluation). The research subjects consisted of 27 fifth-grade students. Data collection techniques included non-test methods (observation, interviews, questionnaires, and documentation) and test methods (pre-test and post-test). Data analysis techniques utilized normality tests, t-tests, and N-Gain tests. This study used Canva and Heyzine to design an integrated PBL-based e-learning material starting with a video stimulus. The feasibility of the e-learning material was demonstrated by a media validation result of 93.75% and a content validation result of 90%, supported by the analysis of teacher and student responses, which categorized it as highly feasible. The effectiveness of the PBL-based e-learning materials was demonstrated by a 30% increase in pre-test and post-test scores; the t-test showed a significance level of 0.000, and the N-Gain was 0.5218, falling into the moderate category. The conclusion of this study is that PBL-based e-learning materials on the subject of flora and fauna biodiversity have been successfully developed, are highly suitable, and are effective in improving the learning outcomes of fifth-grade students at SDN Ngaliyan 05 in Semarang City.